Mathematical Misconceptions of Senior High School Students: Implications to Mathematics Curriculum - Quinio, Karen (JPAIR Institutional Research, 2023)
Misconceptions often pose significant barriers to effective mathematics learning. This study aimed to investigate the misconceptions prevalent in general mathematics and statistics and probability among senior high school students taught during the modular learning modality. Through a mixed-methods approach, involving quantitative surveys and qualitative interviews, mathematical misconceptions such as procedural knowledge, misapplication of formulas, internal barriers, misleading assumptions, and limited question understanding were identified. The study highlights the implications of these findings for curriculum design, teacher professional development, student-centered instruction, and the development of supplementary resources. Moreover, the study underscores the need for tailored interventions to rectify misconceptions, cultivate a deeper understanding of mathematical concepts, and foster accurate probabilistic reasoning among senior high school students during the new normal mode of instruction.
Keywords: general mathematics; misconceptions; modular learning modality; statistics and probability; senior high school students